Experiencing deficit: Multilingual international undergraduate students talk identity - Tavares, Vander (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
This article explores the identity-related experiences of three multilingual international students at a university in Canada. Multilingual international students who speak English as an additional language (EAL) are traditionally referred to as English as a second language (ESL) students. This ESL identity category can negatively impact the social, psychological, and academic experiences of multilingual EAL international students. The three students’ experiences were accessed through in-depth interviews, and insights from post-structuralist theory on identity were drawn on to contextualize them. The findings illustrate that the students experienced a strong sense of deficit on the basis of their positions as ESL students, non-native speakers, and international students. This deficit manifested in experiences of inferiority, otherness, and marginalization.